Thermal Analysis and Early Design Considerations for ESA's ProSPA Package on-board the Roscosmos Luna-27 Lander - Tipper, Emily; Hager, Philipp; Quinn, Andrew (2020 International Conference on Environmental Systems, 2020)
Emily Tipper, Airbus Defence and Space Ltd., GB Andrew Quinn, Airbus Defence and Space Ltd, GB Philipp Hager, European Space Agency (ESA), NL ICES102: Thermal Control for Planetary and Small Body Surface Missions The proceedings for the 2020 International Conference on Environmental Systems were published from July 31, 2020. The technical papers were not presented in person due to the inability to hold the event as scheduled in Lisbon, Portugal because of the COVID-19 global pandemic. The Roscosmos led lunar mission, Luna-27, aims to send a lander to the Moon's south pole. Its scientific objective is to detect and characterize lunar volatiles in polar regions of the Moon. In addition, the mission aims to investigate the potential use of natural lunar resources. Europe’s participation in the mission, led by ESA, includes providing the 'PROSPECT' science package. This consists of a drill, ProSEED, and a sample handling and analysis package, ProSPA. To achieve the science objectives, PROSPECT has the challenging task of retrieving and analyzing samples from cold regions beneath the lunar surface. The volatiles collected will be cold-trapped in the regolith at temperatures expected to be at or below -150 °C. After collection, the ProSPA laboratory unit conducts thermochemical processes at temperatures up to 1000°C to extract and analyze volatile chemical species. Engineering challenges stem from designing a thermal system that is able to preserve samples close to their < -100°C environment temperature during retrieval under very limited volume, mass and power constraints. The system must then be capable of heating the samples to temperatures approaching 1000°C. This paper presents the thermal design concepts considered for ProSPA during Phase B investigations conducted by Airbus Stevenage, UK. Modelling of the lunar environment and transient thermal analysis of the 28 earth-day equivalent lunar day is described. The analysis shows that design efforts are limited by the local environment and restrictions ...